IMPLEMENTASI CONTEXT AWARE PADA SISTEM TRAVEL PLANNER BERBASIS MOBILE - Viery Darmawan; Rengga Asmara; Ira Prasetyaningrum (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
In the era of technological advances, tourists will first seek information about the tourist object to be addressed, even tourists often don't have a destination, so they have to search one by one via the internet. In determining travel plans, it is often to see one by one the review of tourist attractions and conclude the results will take a long time, while tourists need actual and fast information to determine the travel plans. In this study, the authors take a new approach, namely by creating a mobile-based travel planner system that compiles travel plans automatically by considering contextual information related to tourist location points, whether of tourist locations during travel days, travel opening and closing hours, so that it will increase travel efficiency without having to do the research manually which takes a long time. The system can also provide travel recommendations based on visitor comments sentiment on Google Places and is equipped with a trip route that will be generated automatically. This research is useful for helping tourists plan their trip actually because of the consideration of contextual information so that it will make it easier and save tourists time.